2001
DOI: 10.1017/s1355838201010184
|View full text |Cite
|
Sign up to set email alerts
|

Altered discrimination of start codons and initiator tRNAs by mutant initiation factor 3

Abstract: IF3 is essential for ensuring the fidelity of the initiation step of translation in bacterial cells. Mutations at residues R99 and R131 in the C-terminal domain of the factor have previously been shown to increase initiation from the noncanonical GUA codon. Here we show that these mutant forms of IF3 fail to discriminate against initiation from many different non-AUG codons. They also enhance the activity of mutant tRNAs carrying changes in the three consecutive G-C pairs that are conserved in the anticodon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 41 publications
6
50
0
Order By: Relevance
“…Mutations in IF3 generally derepress spurious initiation by fivefold to 40-fold (Table 1; (Sacerdot et al 1996;Sussman et al 1996;O'Connor et al 2001), while the effects of G1338A are twofold or less (Table 1). Furthermore, the ability of IF3 to discriminate the start codon does not depend on the Type II ''G-minor'' interaction, because the degree of repression by IF3 (infC+ versus infC362) is comparable for ribosomes harboring either G or A at position 1338 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in IF3 generally derepress spurious initiation by fivefold to 40-fold (Table 1; (Sacerdot et al 1996;Sussman et al 1996;O'Connor et al 2001), while the effects of G1338A are twofold or less (Table 1). Furthermore, the ability of IF3 to discriminate the start codon does not depend on the Type II ''G-minor'' interaction, because the degree of repression by IF3 (infC+ versus infC362) is comparable for ribosomes harboring either G or A at position 1338 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nterminal sequencing of polypeptide products of spurious initiation events indicated that, in infC and wild-type strains, translation began with the initiator tRNA (O'Connor et al 1997(O'Connor et al , 2001). Moreover, spurious initiation was observed specifically from codons termed Class IIA (i.e., AUA, AUC, AUU, ACG, and CUG) (Sacerdot et al 1996;Sussman et al 1996), which differ from cognate start codons (AUG, GUG, or UUG) at only one position.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IF3 has been shown to play a significant role in start codon selection. 32,33,34 To examine the possibility that the hyperactive phenotype produced by mutations at 966 and 967 is due to an effect on IF3 binding, we cloned IF1, IF2 and IF3 into a pACYC177 35 derivative constructed in our lab, pKAN6, and placed them under control of the inducible araBAD promoter. 36, 37 As a negative control, we also measured the effect of initiation factor over-expression on GFP translation by ribosomes containing the G693U mutation in 16S rRNA.…”
Section: Mutations At M 2 G966 and M 5 C967 Produce Hyperactive Ribosmentioning
confidence: 99%
“…The other involves an error in start codon selection, where fMet-tRNA pairs with a codon other than the correct start codon. N-terminal sequencing of products of spurious initiation events suggests that translation in these cases begins with fMet-tRNA (O'Connor et al 1997(O'Connor et al , 2001). Furthermore, spurious initiation has been observed to occur from codons termed Class IIA (e.g., AUA, AUC, AUU, ACG, and CUG), which differ from the cognate AUG at only one position (Sacerdot et al 1996;Sussman et al 1996).…”
Section: Introductionmentioning
confidence: 99%